Advanced solving techniques in optimization of machine components - Haase, Gundolf; Lindner, Ewald H. (Computer Assisted Methods in Engineering and Science, 2023)
We consider the optimal design of a machine frame under several stress constraints. The included shape optimization is based on a Quasi-Newton Met hod and requires the solving of the plain stress state equations in a complex domain for each evaluation of the objective therein. The complexity and robustness of the optimization depends strongly on the solver for the pde. Therefore, solving the direct problem requires an iterative and adaptive multilevel solver which detects automatically the regions of interest in the changed geometry. Although we started with a perfected type frame we achieved another 10 % reduction in mass.